A Rhizomatic Approach in Elementary Reading Comprehension Strategies: Encouraging Dynamic Connections with Local Literature - Ismail, Ismail; Khalid, Muh. Idham; Mahyuddin, Muhammad Junaedi; Musdalifah, Musdalifah; Djafar, Suarti; Suparman, Suparman (CV ALFA EDU KARYA, 2024)
This study explores the effectiveness of a rhizomatic approach in enhancing reading comprehension through the integration of local literature at SD Negeri 161 Enrekang, South Sulawesi, Indonesia. Literacy skills, particularly reading comprehension, are critical for academic success, yet traditional teaching methods often fail to engage students or foster critical thinking. While rhizomatic learning has proven effective in higher education, its application in primary education remains underexplored. This study employed a mixed-methods design, incorporating classroom observations, analysis of students' written responses, and pre-test and post-tests to measure the impact of this approach on student engagement and comprehension. The findings revealed significant improvements in reading comprehension, with students demonstrating greater engagement and the ability to make personal and cultural connections with the texts. These results suggest that the rhizomatic approach, integrated with local literature, can create a more interactive and meaningful learning experience for young learners. The study emphasizes the importance of culturally relevant texts in enhancing literacy skills and provides insights into the potential of non-linear learning frameworks in primary education. Further research is recommended to examine the long-term effects and scalability of this approach.